Investigating a framework to facilitate the implementation of city development strategy using balanced scorecard - Rasoolimanesh, Mostafa S.; Jaafar, Mastura; Badarulzaman, Nurwati; Ramayah, T. (ELSEVIER, 2015)
This paper examines a framework for facilitating the implementation of City Development Strategy (CDS). Two facets of this framework are explored; factors deduced from previous CDS experiences as having an influence on strategy implementation, and the balanced scorecard (BSC), which is a method commonly used to bridge the gap between strategy formulation and implementation. A questionnaire survey was administered to collect data from stakeholders in the CDS planning process. Partial least squares-structural equation modeling (PLS-SEM) was employed for data analysis. The results of the structural model indicated that stakeholders, financial management, institutionalization, capacity building, and leadership have significant positive effects on CDS implementation. The findings also revealed a significant causal relationship between the factors adopted from the BSC model. This study contributes to the CDS implementation literature by examining the impact of stakeholders, financial management, institutionalization, capacity building, and leadership on future CDS implementation. On a more practical level, these findings contribute to the expanding body of knowledge concerning how to implement CDS successfully in the Iranian context.